Penerapan Model Pembelajaran Active Knowledge Sharing Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Geografi Kelas X - Amrin, Fidya Hidayah; Maryati, Sri; Yusuf, Daud (-, 2025)
The purpose of this study is to improve student learning outcomes through the Application of the Active Knowledge Sharing Learning Model in geography learning on atmospheric dynamics material. This research was conducted at Moosalamati Integrated Islamic High School. This research is a classroom action research (CAR). The data collection technique is by using a learning outcome test in the form of objective (Multiple Choice) which is given to the research sample. The research sample consisted of 16 students in class X in the Geography subject on atmospheric dynamics material using the Active Knowledge Sharing learning model. Based on the results of the study, the implementation of this classroom action research consists of 2 cycles, namely cycles 1 and II. The results of the analysis in cycle 1 showed that out of 16 students who were subjected to the action, 5 people completed it, reaching 31.25% and people who did not complete it, reaching 68.75%. The percentage of completion class increased in cycle II where 16 students who were subjected to the action, 13 people completed it or reached 81.25% and 3 people who did not complete it or reached 18.75%. The conclusion of this study is that the use of the Active Knowledge Sharing learning model can improve student learning outcomes in Geography learning on atmospheric dynamics material at Moosalamati Integrated Islamic High School.